The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s12105-017-0829-7
|View full text |Cite
|
Sign up to set email alerts
|

Low Grade Carcinoma Ex-Pleomorphic Adenoma: Diagnosis and Diagnostic Challenges Caused by Fine Needle Aspiration: Report of Three Cases and Review of Literature

Abstract: Low grade carcinoma ex pleomorphic adenoma (LG CXPA) is a rare low grade malignant neoplasm arising from preexisting pleomorphic adenoma (PA). LG CXPA demonstrates no overt cytological atypia, and can be difficult to distinguish from cellular PA. Invasive growth is one of the hallmarks of LG CXPA, e.g., tumor extends beyond the capsule and into adjacent non-neoplastic tissue. However, it is known that capsular and vascular invasion, as well as the presence of stroma-rich PA in soft tissue without a capsule (ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Until 1999, the FNA findings in only 41 cases of carcinoma ex pleomorphic adenoma had been reported 3 . Since then, 33 additional cases with modern classification criteria have been retrieved from the literature 2‐4,9,16,17 . Of these, 19 showed non‐MED and 14 (including our case) showed MED (Table 1).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Until 1999, the FNA findings in only 41 cases of carcinoma ex pleomorphic adenoma had been reported 3 . Since then, 33 additional cases with modern classification criteria have been retrieved from the literature 2‐4,9,16,17 . Of these, 19 showed non‐MED and 14 (including our case) showed MED (Table 1).…”
Section: Discussionmentioning
confidence: 93%
“…Klijanienko et al, 3,12 reported 26 cases: 19 showing non‐MED and seven with MED (three epithelial‐myoepithelial carcinomas, one basal cell adenocarcinoma, one polymorphous low‐grade carcinoma, and two adenoid cystic carcinomas). Covinsky et al 17 described three cases of low‐grade pleomorphic adenocarcinoma arising in pleomorphic adenoma, all with MED. All three cases were false‐negative on cytological FNA.…”
Section: Discussionmentioning
confidence: 99%
“…When malignancy is suspected, the diagnostic modality of choice is the FNA. Although it is a fast, safe, and cost-effective choice, it has limitations that are mainly attributed to sampling errors [ 13 ]. Core-needle biopsy under ultrasound guidance has been described as an accurate and safe method of diagnosing salivary gland tumors, with some studies providing significant superiority compared to FNA [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to excisional biopsy, FNAB is quick, simple, and minimally invasive. Moreover, FNA studies significantly reduce complications, including facial nerve damage, tumor implantation, fistula formation, and tissue reactions, which make subsequent surgery difficult . Meanwhile, a serious matter remains in FNA studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FNA studies significantly reduce complications, including facial nerve damage, tumor implantation, fistula formation, and tissue reactions, which make subsequent surgery difficult. 13 Meanwhile, a serious matter remains in FNA studies. Several studies have demonstrated that the sensitivity of FNAC when diagnosing Ca-ex-PA is 29%-50% and that the reliability has never been shown to be high.…”
Section: Discussionmentioning
confidence: 99%